Antibacterial Ability of Rhizophora mucronata Leaf Extract Against Bacterial Infections of Edwardsiella tarda - Rizal Rifa'i, Ramanda Ahmad; Andayani, Sri; Fadjar, Mohamad (Graduate School, Universitas Brawijaya, 2023)
Edwardseilla tarda is a group of gram-negative bacteria with facultative anaerobic properties that can infect both cultivated and wild fish. Edwardseilla tarda infection causes considerable economic losses in the world. Rhizopora mucronata is a plant that is known to have the ability to produce secondary metabolites such as alkaloids and flavonoids. This study aims to determine the ability of R. mucronata to inhibit the growth of E. tarda as indicated by the presence of an inhibition zone and the absorbance value in the tube dilution test. The method used in this study is the disc diffusion test and the tube dilution test. The results of the phytochemical analysis showed the presence of flavonoid and alkaloid compounds in the crude extract of R. mucronata leaves. A concentration of 15.6 mg.L-1 showed a minimal inhibitory response in inhibiting the growth of E. tarda bacteria. In comparison, the concentration of 56 mg.L-1 showed the highest inhibitory response in inhibiting the growth of E. tarda bacteria. It indicates that the compounds contained in R. mucronata can be used as alternative ingredients in medicine to treat E. tarda bacterial infections. Keywords: Alkaloid, Antibacterial, E. tarda, Flavonoid, R. mucronata.